Air layering in cinnamon (Cinnamomum verum L.) under wet humid tropical conditions - P Bohra, A A Waman, (Journal of Spices and Aromatic Crops, 2018)
Cinnamon is a cross pollinated species and seed propagation has resulted in development of considerable variability in growth, yield and quality among the populations. Air layering has been considered as one of the efficient methods of multiplication in cinnamon. However, the success of layering varies greatly depending on the local environmental conditions. In the present investigation, air layering was performed at 20 days interval during rainy season (July 3rd to October 11th) of two consecutive years in Bay islands. Result revealed that first week of July was the most suitable time for air layering in cinnamon as it supported better rooting percentage (87.5%).